Effectiveness of Inventory Internal Control System in the UK IT Retail Industry - Chia, Sak Chan (2005)
With its dynamism, IT industry as a whole is consistently moving at a captivating and rapid pace. The storm waves launching of new products has swamped the entire IT market. For approximately 2 decades of grooming, the market, is now, however, suffocated by its overloaded participants over competitive. As a result market is no longer enjoying healthy profit margin as before and currently sustains at a fierce environment. UK IT retail market is at its mature stage, it will not be an easy task to penetrate the UK IT retail market without well preparation.